METODE TUTOR SEBAYA UNTUK MENINGKATKAN KETERAMPILAN SISWA DALAM MEMAINKAN GAMELAN DEGUNG KREASI DI SMPN 1 BAREGBEG - Novianti, Rahyuni; Supriatna, Nanang; Karwati, Uus (Program Studi Pendidikan Seni Musik UPI, 2023)
Problems that occur in class VIII-A have difficulty playing the gamelan creations of the flower implengan song, then there are still many students who are less active and hesitate to ask the teacher so that students' skills are less focused. The purpose of this study was to determine the results of the application of the peer tutor method on students' skills in playing the waditra gamelan. The criteria for students who become tutors are students who have skills that are superior to others and have a friendly personality and a high sense of responsibility. The method used in this classroom action research is a descriptive method with a qualitative approach. The research subjects were all students of class VIII-A, totaling 28 students. The material taught is the song flower implengan created by Nano s. The positive impact of the application of the peer tutoring method is that students become confident, become active, friendships become more intimate, while the negative impact of the application of the peer tutoring method is that some tutors are not good friends with students. Thus, it is concluded that the peer tutoring method can improve the learning of gamelan gamelan creations in class VIII-A students of SMPN 1 Baregbeg.Keywords: skills, peer tutor method, degung gamelan creations